한국 자생나리의 기내 인편삽에 의한 Lily Symptomless Virus 제거 및 구근 재배조건에 따른 재감염 분석 - 김규원(Kiu Weon Kim); 김민희(Min Hui Kim); 박인숙(In Sook Park); 박경일(Kyeung Il Park); 오욱(Wook Oh) (Weon'ye gwahag gi'sulji, 2015)
The lily symptomless virus (LSV) is the most common virus in Korean native lilies and causes various types of damage to overall plant growth. This study was carried out to investigate the elimination rate of the LSV by the in vitro scale culture (scaling) method in Korean native lilies and to test reinfection rates of the LSV under several field culture conditions of bulb production. Four Korean native lilies (Lilium dauricum, L. distichum, L. lancifolium, and L. maximowitzii) were used and their scales were cultured in vitro for micro-scale formation. The micro-scales were subcultured repeatedly using MS culture medium supplemented with 30 or $90g{·}L^{-1}$ sucrose. The culture conditions were $24μmol{·}m^{-2}{·}s^{-1}$ PPFD with 16 hour daylength using fluorescent lamps and maintained at $22{±}2^{°}C$. The virus-free bulblets were grown for one to three years in the greenhouse and transplanted to the field in October or March. Virus infection rates were investigated by direct tissue blotting immunobinding assays and measurement of chlorophyll and protein contents. Virus-free plants could be obtained from the 5th subculture of micro-scales in L. lancifolium and L. maximowitzii or from primary culture in L. dauricum and L. distichum. LSV-free plants were reinfected during bulb production in the field. Reinfection rates were higher at older bulb ages and under higher planting density. The plants planted in October and at inland Gyeongsan had higher infection rates than those planted in March and at coastal area Pohang. The reinfection rate of L. maximowitzii was higher than those of L. dauricum and L. lancifolium. The LSV-infected plants had lower chlorophyll contents and unchanged protein contents compared to virus-free plants. 본 연구는 자생나리에 있어서 기내 인편삽의 계대배양이 lily symptomless virus(LSV) 제거에 미치는 영향과 구근 재배 조건이 LSV 재감염에 미치는 영향을 구명하여 LSV 무병주 대량 생산을 위한 기초자료를 제공하기 위하여 실시되었다. 식물재료로는 날개하늘나리(L. dauricum), 말나리(L. distichum), 참나리(L. lancifolium), 중나리(L. maximowitzii)등 자생나리 4종을 사용하였다. LSV에 감염된 식물체의 인편에서 소인경을 얻은 다음 이들 소인경을 5회 이상 계대배양을 했을 때 LSV가 완전히 제거되었다. 특히 날개하늘나리와 말나리에서는 1회 기내 인편삽으로도 LSV를 완전히 제거할 수 있었다. 그러나 기내배양을 통해 생산된 LSV 무병주라도 구근의 재배기간이 길수록, 봄 정식구보다 가을 정식구에서, 소식구보다 밀식구에서, 해안지역보다는 내륙 지역에서 재감염률이 높았다. 그리고 재감염률은 중나리가 날개하늘나리와 참나리보다 높았다. LSV 감염주는 무병주에 비해 엽록소 함량이 낮았다. 따라서 자생나리 구근의 수회 계대배양을 통해 LSV를 제거할 수 있으며, 구근 생산과정에서 낮은 재식밀도, 봄 정식, 해안지역 정식 등 재배적 방제를 통해 LSV 재감염을 억제할 수 있을 것이다.